Tumor necrosis factor-like weak inducer of apoptosis expression in healthy oral mucosa, oral dysplasia and oral squamous cell carcinoma - Acharya, Swetha (J Oral Maxillofac Pathol, 2019)
OBJECTIVE: Tumor necrosis factor-like weak inducer of apoptosis (TWEAK) has been implicated in the pathogenesis of cancer, as it participates in the progression of internal malignancies. However, its role in the biology of squamous cell carcinoma (SCC) is uncertain. Studies regarding TWEAK in SCC have shown inconsistent results. We aimed to study the expression of TWEAK in healthy oral mucosa, oral dysplastic lesions and in oral SCC (OSCC). METHODS: Immunohistochemistry for TWEAK was performed on one hundred oral mucosal tissues, healthy control (HC) (n = 20), oral dysplasia (OD) (n = 20) and OSCC (n = 60). Staining intensity, extent of staining (ES) and immunoreactive Score (IRS) were assessed for each sample. Kruskal–Wallis ANOVA, Mann–Whitney U, Chi-square and Spearman's rank correlation coefficient were applied. RESULTS: TWEAK was expressed in 55% of HC, 90% of OD and in all cases of OSCC, with variable intensities. A significant difference in the ES and IRS of TWEAK was noted among the three groups. ES and IRS were highest in OSCC group. ES of TWEAK was significantly higher at invasive tumor front (ITF) than in the whole tumor, with a significant positive correlation. TWEAK expression showed a significant association with invasive front grading, pattern of invasion and surgical margins of OSCC. CONCLUSIONS: TWEAK may contribute to the progression of OSCC. It might also sustain altered differentiation, invasion and migration of tumor cells at ITF.